2009
DOI: 10.1507/endocrj.k08e-332
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Systemic Oxidative Stress to Body Fat Distribution, Adipokines and Inflammatory Markers in Healthy Middle-aged Women

Abstract: Abstract. Obesity and systemic oxidative stress are closely related. however data concerning the relationships between oxidative stress and body fat mass distribution are sparse. Anthropometric and metabolic profile was evaluated in 148 clinically healthy middle-aged women to assess the correlations between oxidative stress, fat mass distribution, adipokines, and inflammatory markers. Systemic oxidative stress was assessed by urinary creatinine-indexed 8-epi-prostaglandin F-2α (8-epi-PGF 2α ). Body fat mass di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 49 publications
1
36
0
1
Order By: Relevance
“…However, in both study groups the blood levels were measured during fasting and all subjects reported stable weight for at least two months prior to inclusion. Few studies have shown the same trend with leptin levels in lean people, but a positive association between fat mass accumulation, oxidative stress indices and leptin levels has been observed, 7 suggesting that fat mass-induced oxidative stress may cause a dysregulation of adipokines, also in lean subjects. A positive relationship between BMI, waist circumference and CRP has been documented.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, in both study groups the blood levels were measured during fasting and all subjects reported stable weight for at least two months prior to inclusion. Few studies have shown the same trend with leptin levels in lean people, but a positive association between fat mass accumulation, oxidative stress indices and leptin levels has been observed, 7 suggesting that fat mass-induced oxidative stress may cause a dysregulation of adipokines, also in lean subjects. A positive relationship between BMI, waist circumference and CRP has been documented.…”
Section: Discussionmentioning
confidence: 95%
“…5 It is well known that inflammatory markers are associated with fat mass in overweight and obese subjects, 6 but this relation between fat mass and inflammatory markers in lean subjects is not well documented. 7 Several methods are used to measure the amount of fat in adults. One of the most accurate methods is Dual-energy X-ray absorptiometry (DXA), 7 but measuring fat this way is costly and not readily available in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Daughters were students of the University and the characteristics of the daughters 10) and their mothers 11) are described in detail elsewhere. Body composition was determined using whole-body DXA (QDR-2000, software version 7.20D; Hologic, Bedford, MA, USA) as previously reported 10) . The software provides estimates of lean tissue mass, fat mass, and bone mineral mass for the total body and for standard body regions.…”
Section: Methodsmentioning
confidence: 99%
“…Estudos mostram que o ganho de peso aumenta a formação de substâncias pró-oxidantes e também mostram que indivíduos obesos tem perfil oxidativo acentuado quando comparados a indivíduos normais. A obesidade tem relação com outros estados mórbidos (hipertensão arterial, resistência à insulina, DM2, dislipidemia e complicações vasculares) que possuem relação com o desencadeamento do desbalanço oxidativo [39][40][41].…”
Section: /7unclassified